The first nymph-imago association and observed biology of the wood-dwelling mayfly Povilla heardi (Hubbard, 1984) from China (Ephemeroptera: Polymitarcyidae: Asthenopodinae) - Zheng, Xuhongyi; Mu, Pengxu; Zhou, Changfa (Journal of Asia-Pacific entomology, 2024)
[Display omitted] •Discovery of Povilla heardi represents the first record of Asthenopodinae in China.•The first nymph-adult association of Asian Povila species is confirmed.•Nymphs of Povilla heardi making tunnels and “ cocoons” in submerged woods.•Nymphs of Povilla heardi were found carrying eggs on their back. Although the species Povilla heardiHubbard, 1984 was described from both males and putative nymphs, no photographic structures were presented, and this species was not found in China before. In 2023, dozens of adults were trapped and reared from nymphs in southwestern Chinese Yunnan Province. Detailed descriptions and photographs of them confirmed the synonym Povilla junki to P. heardi, and represent the first nymph-adult association of Asian species in the genus. In addition, our findings represent the first record of Asthenopodinae in this country, widened the Northern distribution of Povilla, and provide some biological information for this poorly known species.